Value of co-benefits from energy saving ventilation systems: Contingent valuations on Swiss home owners - Nina Boogen; Massimo Filippini; Adán L. Martínez-Cruz (ETH Zurich, CER-ETH - Center of Economic Research, 2022)
Previous efforts exploring options to increase residential sector's energy efficiency have overlooked that highlighting co-benefits associated with energy efficiency may represent a promising strategy to draw attention from decision makers. For instance, in addition to savings in energy costs, buildings equipped with energy saving and comfort ventilation (ESV) system provide co-benefits such as improved indoor air quality (IAQ), thermal comfort, and noise reduction. These co-benefits are attributes of an experience goods as their value is difficult to appraise unless they have been experienced. This paper estimates the value of these co-benefits by inquiring willingness to accept (WTA) compensation to hold off on using ESV from Swiss owners of Minergie houses, which are equipped with ESV. Average monthly WTA is CHF 181 - value dominated by IAQ. WTA protocols may deliver overestimated values. Thus this paper estimates willingness to pay (WTP) on a sample of owners of conventional houses - i.e. respondents that have not experienced an ESV. Average monthly WTP is CHF 163 - value dominated by presence of allergies at home, an approximation to relevance of IAQ among respondents that have not experienced ESV. A back-of-the-envelope cost-benefit analysis informed with our estimates suggests that monthly benefits from ESV can be as much as twice the costs.
Keywords: D12; Q40; R21; 330; co-benefits of energy efficiency; residential investment decisions; willingness to accept; willingness to pay; Swiss home owners